Non licensure practices in allopathy hospitals of Southern India - Infamous conduct - Karthik S.K. MD2, Dr. Jayaprakash G. MD3, Dr. Mohan V.J.4, Dr. Balaji P.A. MD, PGDMLE (NLSIU) 1, *Dr. Syed Sadat Ali, MD,DHHM1, Dr. (International Multidisciplinary Research Journal, 2011)
Health is a basic and primary need of a human being. With increase in population the health needs of the people are on rise but in many cases they are inadequately met. To maintain health in India different systems of medicine such as allopathy, homoeopathy, ayurveda, siddha, unani, etc are practiced. Indian law states that, a person trained and registered under a particular system of medicine should practice only that system and not the alternate system. But in recent times non-allopaths who are not licensed to practice have started practicing allopathy which is infamous conduct. [1] A survey was carried out in 40 allopathy nursing homes at bengaluru city. We found that on an average only 18 [12.41 %] of the duty doctors in the wards and casualty were holding medical degrees in MBBS and a maximum number 116 [87.59 %] were Ayurveda, homeopathic and unani degree holders and only 170 [34.94 %] of the nurses were qualified while maximum 280 [65.05%] were unqualified (meaning they had no degrees of any kind and they were just given some informal training in the hospital). In spite of presence of qualified consultants, this type of non licensure practice may hinder the quality of medical services.